Phase-Preserving 2R-Regeneration of a WDM RZ-DPSK Signal Using a Nonlinear Amplifying Loop Mirror - Cvecek, Kristian; Sponsel, Klaus; Stephan, C.; Onishchukov, Georgy; Ludwig, R.; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication / National Fiber Optic Engineers Conference OFC/NFOEC 24.-28.02., 2008)
A modified NALM setup for phase-preserving amplitude regeneration of WDM-DPSK signals is proposed. Demultiplexing-multiplexing within the NALM fiber loop is used to avoid WDM channel crosstalk, A negative power penalty of 1.2 dB was obtained. © 2007 Optical Society of America.
UnivIS-Import:2017-11-07:Pub.2008.tech.IE.LEH.phasep